Sitotoksisitas rimpang temu mangga (Curcuma Mangga Val. & V. Zijp.) dan kunir putih (Curcuma Zedoaria L) terhadap beberapa sel kanker manusia (in vitro) dengan metoda SRB - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Mae Sri Hartati W, Sofia Mubarika, R. L. H. Bolhuis, K. Nooter, R. G. Oostrum, A. W. M. Boersma, Subagus Wahyuono - Cytotoxic effect on human cancer cell using SRB method (in vitro) rimpang temu mangga (Curcuma Mangga Val. & V. Zijp.) dan kunir putih (Curcuma Zedoaria I.). Background: Temu mangga (Curcuma mangga) and kunir putih (Curcuma zedoaria) rhizomes have been utilized by people to treat cancer lately although clinically their activity has not been tested. Objectives: This study is aimed to prove their activity as anticancer on 7 major human cancers cell lines (in vitro), and to evaluate whether these two rhizomes are potential for new anticancer drug. Methods: The two rhizomes were separately extracted with chloroform followed by methanol to give chloroform extracts of C. mangga (CmCh) and C. zedoaria (CzCh)